2016
DOI: 10.1187/cbe.16-01-0038
|View full text |Cite
|
Sign up to set email alerts
|

Improving Underrepresented Minority Student Persistence in STEM

Abstract: Members of the Joint Working Group on Improving Underrepresented Minorities (URMs) Persistence in Science, Technology, Engineering and Mathematics (STEM), utilizing Kurt Lewin’s planned approach to change, describe five recommendations to increase URM persistence in STEM at the undergraduate level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
425
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 469 publications
(495 citation statements)
references
References 34 publications
8
425
0
Order By: Relevance
“…Research on diversifying Chemistry [17] and STEM more generally [19,20] has focused largely on recruitment of women and URM students into graduate programs, as well as these students’ progress towards (and completion of) the Ph.D. This research highlights several important best practices for recruitment and retention efforts, including a visible commitment from institutional administrators, targeted scholarships, strong mentoring, and systematic benchmarking of both student progress and institutional goals.…”
Section: Discussionmentioning
confidence: 99%
“…Research on diversifying Chemistry [17] and STEM more generally [19,20] has focused largely on recruitment of women and URM students into graduate programs, as well as these students’ progress towards (and completion of) the Ph.D. This research highlights several important best practices for recruitment and retention efforts, including a visible commitment from institutional administrators, targeted scholarships, strong mentoring, and systematic benchmarking of both student progress and institutional goals.…”
Section: Discussionmentioning
confidence: 99%
“…Science faculty and institutions have been called to “unleash the power of the curriculum” in order to address differential STEM attrition rates, particularly for HU students in entry‐level undergraduate courses (Estrada et al., ). By building partnerships across institutions, faculty have become instructional innovators that significantly shift undergraduate STEM education to increase critical thinking and agency (see the Partnership in Undergraduate Life Science Education [PULSE], the Association of American Universities Undergraduate STEM Education Initiative, and Science Education for New Civic Engagements and Responsibilities [SENCER] <http://sencer.net/> for examples) (Kezar, & Gehrke, ).…”
Section: Current Research On Successful Approaches To Creating Socialmentioning
confidence: 99%
“…Specifically, we recommend collecting and tracking student data including (a) department level disaggregated demographic information (e.g., ethnicity/race, gender, socioeconomic status, first generation status), (b) participation in research training and support program, (c) mentorship, and (d) outcomes typically already tracked such as course progression, degree attainment, and time to degree. In support of this, funding agencies can require STEM degree attrition and attainment data from institutions that receive support in a standardized format that identifies disparity and equity (see Estrada et al., or recommendations in the National Academy of Sciences report, ). Posting summaries of this type of data on college and university websites also provides transparency and usability of the information.…”
Section: Research As a Way To Initiate And Sustain Changementioning
confidence: 99%
See 1 more Smart Citation
“…This might be a potentially fruitful area for future research, as we found no literature that specifically addresses non-STEM students in STEM courses. However, there is research that suggests that there are many students, especially women and underrepresented groups, who can succeed in STEM courses but fail to do so for non-cognitive reasons, such as a lack of self-efficacy or confidence [5][6][7].…”
mentioning
confidence: 99%